Exploring the relationship between intestinal microbiota and immune checkpoint inhibitors in the treatment of non-small cell lung cancer: insights from the “lung and large intestine stand in exterior-interior relationship” theory - Li, Luwei; Zhong, Hongmei; Wang, Yajie; Pan, Zongying; Xu, Shumei; Li, Shuai; Zeng, Guilin; Zhang, Weiwei; Li, Jie; He, Lang (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: This study is aim to discern the Traditional Chinese Medicine (TCM) syndrome classifications relevant to immunotherapy sensitive in non-small cell lung cancer (NSCLC) patients, and to delineate intestinal microbiota biomarkers and impact that wield influence over the efficacy of NSCLC immunotherapy, grounded in the TCM theory of "lung and large intestine stand in exterior-interior relationship." Methods: The study cohort consisted of patients with advanced NSCLC who received treatment at the Oncology Department of Chengdu Fifth People's Hospital. These patients were categorized into distinct TCM syndrome types and subsequently administered immune checkpoint inhibitors (ICIs), specifically PD-1 inhibitors. Stool specimens were collected from patients both prior to